New geophysical data about the inner structure of Drake Passage crust - Levashov, S.; Korchagin, I.; Kozlenko, Yu.; Solovyov, V. (Ukrainian Antarctic Journal, 2006)
The Ukrainian Antarctic expeditions 1997-2004 years provided new geophysical data for many West Antarctica bottom structures. Gravity, magnetic- and electromagnetic surveys of Drake Passage made near the Antarctic Peninsula also. New obtained results for the tectonic structures enabled to specify the age of the formation of some blocks, separate local crustal inhomogeneities, specify the schemes of the structural division of the continental margin of Antarctica. A great effect of the tectonic factors on the formation of the inhomogeneous sediments (100m to 2,5km thick) and existence of some intrusion zones and tectonically active fracture zones in Drake Passage has been detected.